Relationship between Socio-Economic with Parent’s Knowledge of Toddler Feeding Patterns - Rida Siti Toyibah; Dadang Purnama; Furkon Nurhakim; Laili Rahayuwati; Desy Indra Yani; Gusgus Graha Ramdhanie (Journal of Nursing Care, 2023)
Parental knowledge about toddler feeding patterns is one of the factors that can affect the incidence of stunting. Knowledge about toddlers' feeding patterns can be influenced by socioeconomic factors such as education level, occupation, and income. This study analyzed the relationship between education level, occupation, and income with parental knowledge of toddler feeding patterns in the stunting locus. This study used a quantitative correlation design with a secondary data approach. The population is the respondent from secondary data, parents with toddlers in Sukamulya Village. The samples were taken using the total sampling technique of 76 people. The variables in the study were education level, occupation, income, and knowledge of child nutrition patterns. The instrument consisted of questions on education level, employment status, income level, and 14 toddler feeding patterns knowledge questions. Statistical test using Chi-square with 5% significance level. The results of the study found that there was no relationship between education level (p-value=0.282), occupation (p-value=0.717), and income (p-value=1.000) with toddler feeding patterns knowledge. It is due to other factors that influence the knowledge of children's eating habits. More research is needed to determine the factors that influence knowledge of children's feeding patterns.